Financial management behavior of junior high school woman teacher - Kautsar, Achmad; Asandimitra, Nadia; Isbanah, Yuyun; Kusumaningrum, Trias Madanika; Rozaq, Khoirur (Technium Social Sciences Journal, 2020)
A large number of female teachers in junior high schools shows that the role of women is becoming increasingly important in the family and society, so it is important for Financial Management Behavior. This type of research is explanative research using a quantitative approach. The sampling technique in this study using snowball sampling, so that 100 respondents were reached who became the respondents of this study. Financial attitude, financial knowledge, locus of control were found to have a significant positive effect on financial management behavior. Materialism was found to have no effect on the financial management of female junior high school teachers in Surabaya. The next finding is that financial knowledge affects the financial management of female junior high school teachers in Surabaya mediated by the locus of control.